2016
DOI: 10.33096/jffi.v2i2.179
|View full text |Cite
|
Sign up to set email alerts
|

UJI AKTIVITAS ANTIOKSIDAN EKSTRAK METANOL BUNGA BROKOLI (Brassica oleracea L. var. Italica) DENGAN METODE DPPH (2,2 diphenyl-1-picrylhydrazyl) dan METODE ABTS (2,2 azinobis (3-etilbenzotiazolin)-6-asam sulfonat)

Abstract: Telah dilakukan penelitian uji aktivitas antioksidan ekstrak metanol bunga brokoli (Brassica oleracea L. var. Italica) dengan menggunakan metode DPPH (2,2-diphenyl-1-picrylhydrazyl) dan metode ABTS (2,2-Azinobis (3etilbenzotiazolin)-6-asam sulfonat). Bunga brokoli diekstraksi secara maserasi dengan menggunakan pelarut metanol. Ekstrak bunga brokoli (Brassica oleracea L. var. Italica) dibuat dalam berbagai konsentrasi dan diuji aktivitas antioksidannya. Pada metode DPPH diperoleh nilai IC50 sebesar 123,698 ppm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
1
4
0
3
Order By: Relevance
“…Another important consideration is that the bioactive compounds (flavonoids and phenolics) present in the corn kernels are in their glycoside form, which has been reported to have weak free radical scavenging activity (Molyneux 2004). Furthermore, the purity of the extract can also affect the antioxidant capacity since the presence of other compounds can weaken the free radical scavenging activity, as previously reported (Sami and Rahimah 2016). In conclusion, Based on the result and discussion, it can be concluded that the Pulut cultivar exhibited the highest total polyphenol content, while the Kuning Dalam cultivar reported the third highest total polyphenol content, the highest total flavonoid content and one of the strongest antioxidant activity.…”
Section: Pearson Correlation Coefficientssupporting
confidence: 67%
“…Another important consideration is that the bioactive compounds (flavonoids and phenolics) present in the corn kernels are in their glycoside form, which has been reported to have weak free radical scavenging activity (Molyneux 2004). Furthermore, the purity of the extract can also affect the antioxidant capacity since the presence of other compounds can weaken the free radical scavenging activity, as previously reported (Sami and Rahimah 2016). In conclusion, Based on the result and discussion, it can be concluded that the Pulut cultivar exhibited the highest total polyphenol content, while the Kuning Dalam cultivar reported the third highest total polyphenol content, the highest total flavonoid content and one of the strongest antioxidant activity.…”
Section: Pearson Correlation Coefficientssupporting
confidence: 67%
“…The yield of evaporation was calculated (20). Then each extract was analyzed for IC-50 antioxidant activity (21,22). Data analysis was carried out descriptively (mean ± standard deviation).…”
Section: Methodsmentioning
confidence: 99%
“…Antioxidant activity was analysed following the method used by Sami and Rahimah (2016). A total of 3 g leaf sample was macerated using methanol (99.8%) for 24 h. After 24 h, the mixture was filtrated using filter paper, and the filtrate was thickened utilising a rotary evaporator.…”
Section: Antioxidant Activity Analysismentioning
confidence: 99%